Investigating depression in multiple sclerosis: an Italian Delphi consensus on clinical manifestations, diagnosis and treatment - Bruno, Antonio; Dolcetti, Ettore; Annovazzi, Pietro; Clerico, Marinella; Cocco, Eleonora; Conte, Antonella; Marfia, Girolama Alessandra; Salvetti, Marco; Tomassini, Valentina; Clerici, Valentina Torri; Totaro, Rocco; Nicoletti, Ferdinando; et al. (Frontiers in Psychiatry, 2025)
BackgroundIn multiple sclerosis (MS), depression represents one of the most frequent psychiatric comorbidities, significantly impacting patients’ quality of life and disease progression. However, the diagnosis and management of depression in MS remain challenging due to overlapping symptoms and the lack of specific treatment guidelines. This Delphi study aims to achieve a shared consensus among Italian MS experts regarding the clinical manifestations, diagnosis, and treatment of depression in MS.MethodsAn online Delphi survey with 35 questions covering the epidemiology, clinical features, diagnostic criteria, and treatment of depression in MS was anonymously administered to a panel of 51 expert neurologists across Italy. The consensus was based on a two-round Delphi process.ResultsConsensus was reached on 100% of the statements. Positive consensus was achieved on 90.6% of the statements, while 9.4% reached negative consensus. Key findings include the strong link between depression and MS, with depressive symptoms often preceding MS onset. The panel agreed that the DSM-5 diagnostic criteria should be adapted to capture the specific mood disturbances seen in MS. Regarding treatment, antidepressants were widely prescribed, but concerns about their efficacy in the MS population remain. Non-pharmacological interventions, such as cognitive behavioral therapy (CBT), were considered essential components of comprehensive care.ConclusionsThis Delphi study highlights the need for tailored diagnostic tools and integrated treatment approaches for managing depression in MS. Further studies are required to refine guidelines for the use of antidepressants and explore the role of disease-modifying therapies (DMTs) in treating depression in this population.